Responsivity of the differential-intensity surface plasmon resonance instrument - Abayzeed, Sidahmed A.; Smith, Richard J.; Webb, Kevin F.; Somekh, Michael G.; See, Chung W. (Elsevier, 2016)
Surface plasmon resonance is used for the sensitive measurement of minute concentrations of bio-analytes and probing of electrochemical processes. Typical refractive index sensitivity, for the intensity approach, is around 10−6 refractive index units (RIUs). A better sensitivity has been suggested by developing a differential-intensity detection method. This method relies on the excitation of surface plasmons using a weakly focused beam with the average angle of incidence equal to the resonance angle, while the reflected light is detected using a bi-cell photodiode. The Bi-cell signal is processed by calculating the difference between its two units, normalized to their sum. This ratio estimates the shift in the resonance angle using a model that represents the resonance curve with a quadratic function. However, this model does not explain the effects of parameters such as the angular width of the excitation beam and the specifications of the sensing structure on the system’s response. This paper presents a detailed evaluation of the responsivity using experimental and theoretical approaches, which can predict the effect of the different parameters, paving the way towards the investigation of a better sensitivity and the optimization of the system’s design for different applications.